Position Paper: Overview of Workplace Bullying in Higher Educational Organizations - Saurabh Gangola; Samiksha joshi (Journal of Clinical Research In HIV AIDS And Prevention, 2021)
Coronavirus disease (COVID-19) outbreak has severely affected the whole world. It has overshadowed all the developmental activities across different countries. The COVID-19 pandemic has negatively affected global economy and has threatened health security of people worldwide. This pandemic have affected environment dynamically. Decrease in economic activities, travelling, transport and traffic restrictions all over the world have led to decreased emissions of greenhouse gases and drop in air and water pollution observed universally. Also more than 40 % of downfall is observed in NO2 concentration in Asia and Europe as compared to 2019. Reduced pollution had a good effect on freshwater aquatic life. The reduction in worldwide aircraft flight directly impact on forecast and decreases 65% of weather prediction. Snow fall was observed even in a summer in India. This pandemic has had a long-term impact, affecting all aspects of human life and halting all developmental processes. Combating the COVID-19 pandemic is currently at the top of the global agenda. Quarantine measures opted for safety of the public have positively affected the environment. Although it has downturned the economic growth drastically, it has also contributed in lowering the pollution. If there is a silver lining to this horrible situation, it may be that it has given us a whiff of the air we will breathe in a low-carbon future.
Keywords: Coronavirus